Predictors of Mortality Among Very Low Birth Weight Infants With Gastrointestinal Perforation. Issue 9 (September 2021) - Reppucci, Marina L.; Hersh, Eliza H.; Khetan, Prerna; Coakley, Brian A.
Background: Gastrointestinal (GI) perforation is a risk factor for mortality in very low birth weight (VLBW) infants. Little data exist regarding pretreatment factors and patient characteristics known to independently correlate with risk of death. Materials and Methods: A retrospective review of all VLBW infants who sustained GI perforation between 2011 and 2018 was conducted. Birth, laboratory, and disease-related factors of infants who died were compared to those who survived. Results: 42 VLBW infants who sustained GI perforations were identified. Eleven (26.19%) died. There were no significant differences in birth-related factors, hematological lab levels at diagnosis, presence of pneumatosis, or bacteremia. Portal venous gas ( P = .03), severe metabolic acidosis ( P < .01), and elevated lactate at diagnosis ( P < .01) were statistically more likely to occur among infants who died. Discussion: Portal venous gas, severe metabolic acidosis, and elevated lactate were associated with an increased risk of mortality among VLBW infants who develop a GI perforation. Further research is required to better identify risk factors.